Aggregating Robots Compute: An Adaptive Heuristic for the Euclidean Steiner Tree Problem - Hamann, Heiko; Wörn, Heinz (The tenth International Conference on Simulation of Adaptive Behavior (SAB'08))

On Faster Integer Calculations Using Non-arithmetic Primitives - Lürwer-Brüggemeier, Katharina; Ziegler, Martin (Unconventional Computing)

The k-Resource Problem on Uniform and on Uniformly Decomposable Metric Spaces - Bienkowski, Marcin; Kutyłowski, Jarosław (Lecture Notes in Computer Science)
We define a natural generalization of the prominent k-server problem, the k-resource problem. It occurs in metric spaces with some demands and resources given at its points. The demands may vary with time, but the total demand may never exceed k. The goal of an online algorithm is to satisfy demands by moving resources, while minimizing the cost for transporting resources. We give an asymptotically optimal O(log(min {n,k}))-competitive randomized algorithm and an O(min {k,n})-competitive deterministic one for the k-resource problem on uniform metric spaces consisting of n points. This extends known results for paging to the more general setting of k-resource. Basing on the results for uniform metric spaces, we develop a randomized algorithm solving the k-resource and the k-server problem on metric spaces which can be decomposed into components far away from each other. The algorithm achieves a competitive ratio of O(log(min {n,k})), provided that it has some extra resources more than the optimal algorithm.

Cryptanalysis of Unbalanced RSA with Small CRT-Exponent - May, Alexander (Advances in Cryptology — CRYPTO 2002)

Low Secret Exponent RSA Revisited - Blömer, Johannes; May, Alexander (Lecture Notes in Computer Science)

Key Revocation with Interval Cover Families - Blömer, Johannes; May, Alexander (Selected Areas in Cryptography)

Dimension Reduction Methods for Convolution Modular Lattices - May, Alexander; Silverman, Joseph H. (Lecture Notes in Computer Science)

A Probabilistic Zero-Test for Expressions Involving Roots of Rational Numbers - Blömer, Johannes (Algorithms — ESA’ 98)

Competitive Maintenance of Minimum Spanning Trees in Dynamic Graphs - Dynia, Miroslaw; Korzeniowski, Miroslaw; Kutyłowski, Jarosław (Proc. of the 33rd International Conference on Current Trends in Theory and Practice of Computer Science (SOFSEM'07))

(Short) Survey of Real Hypercomputation - Ziegler, Martin (Lecture Notes in Computer Science)